Chiral Lipid Bilayers are Enantioselectively Permeable - Hu, Juan (Nat Chem, 2021)
Homochiral membrane bilayers organize biological functions in all domains of life. The membrane’s permeability–its key property–correlates with a molecule’s lipophilicity, but the role of the membrane’s rich and uniform stereochemistry as a permeability determinant is largely ignored in empirical and computational measurements. Here, we describe a new approach to measuring permeation using continuously generated microfluidic droplet interface bilayers (DIBs, 480/min) and benchmark this system by monitoring fluorescent dye DIB permeation over time. Permeation of non-fluorescent, alkyne-labeled molecules was measured using a fluorogenic click reaction. DIB transport measurements revealed enantioselective permeation of alkyne-labeled amino acids (Ala, Val, Phe, Pro) and dipeptides through a chiral phospholipid bilayer; the biological L enantiomers permeated faster than D (1.2–6-fold; Ala–Pro). Enantioselective permeation both poses a potentially unanticipated criterion for drug design and offers a kinetic mechanism for the abiotic emergence of homochirality via chiral transfer between sugars, amino acids, and lipids.